Pengaruh Free Cash Flow, Operating Cash Flow, dan Dividend Payout Ratio Terhadap Nilai Perusahaan - Suwaldiman Suwaldiman (Ultima Accounting : Jurnal Ilmu Akuntansi, 2018)
This research examines the impact of free cash flow, operating cash flow, and dividend payout ratio on the firm value which is represented by stock return. This research employees a multiple linear regression analysis to test the hypothesis. Samples used in this research are 159 manufacturing companies registered in Indonesia Stock Exchange for the period of 2013, 2014, and 2015. This research reveals that free cash flow and operating cash flow have no significant impact on the firm value. Those variables seem having no important contents in the point of view of investors. Therefore they do not response to the information. However, this research proves that dividend payout ratio have significant impact on the firm value. It can be concluded that dividend payout ratio is more important than those of free cash flow and operating cash flow. Investors will positively response to the dividend information and it will significantly increase the firm value.